Experimental study on a chemisorption refrigeration system prototype using expanded graphite/activated carbon/lithium chloride-ammonia working pair in a solution of 25% NH3 (2019)
This paper presents the experimental results given by the operation of a chemical sorption refrigeration system using Expanded Graphite/Activated Carbon/Lithium Chloride (AC/GE/LiCl)-Adsorbent (NH3 in solution with a 25% concentration). Experimental protocol with the characteristics of the experimental rig developed, working pair specifications and the procedure that has developed in the process is described in detail. Results are presented for different behaviors of the system, where the desorption stage is driven by forced convection. Measurements of the thermal variables of the system show that the adsorption-desorption cycles in the test accomplished, with high and low-pressure zones clearly defined. The cooling effects for the pair material studied have the expected behavior for the mixture proposed.